Reproductive strategies of three native earthworm species from the savannas of Carimagua (Colombia) - Jiménez Jaén, J.J.; Moreno, Alonso; Lavelle, Patrick M. (International Center for Tropical Agriculture, 2001)
Data on the reproductive biology of three native glossoscolecid species from the Colombian Llanos are presented here. The seasonal dynamics of reproduction varied among the species considered which displayed either one or two reproductive periods per year. Cocoons were laid at different depths to a maximum of 50 cm. The relation between cocoon weight and adult weight was the same for two endogeic species, ca. 6%, whereas for the anecic species the relationship observed was the highest obtained to date for any tropical or temperate earthworm, i.e 16%.